2016
DOI: 10.18632/oncotarget.9666
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ACLY sensitizes castration-resistant prostate cancer cells to AR antagonism by impinging on an ACLY-AMPK-AR feedback mechanism

Abstract: The androgen receptor (AR) plays a central role in prostate tumor growth. Inappropriate reactivation of the AR after androgen deprivation therapy promotes development of incurable castration-resistant prostate cancer (CRPC). In this study, we provide evidence that metabolic features of prostate cancer cells can be exploited to sensitize CRPC cells to AR antagonism. We identify a feedback loop between ATP-citrate lyase (ACLY)-dependent fatty acid synthesis, AMPK, and the AR in prostate cancer cells that could c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 81 publications
2
52
0
Order By: Relevance
“…For instance, in CRPC cells, inhibition of ACLY disrupts ER and energy homoeostasis in CRPC cells, leading to AMPK activation and sensitisation to androgen receptor inhibitors. 213 Intriguingly, supplementation of exogenous FAs is sufficient to restore hormone resistance in CRPC cells by alleviating the ER and energy stress instigated by ACLY inhibition, demonstrating the importance of an ACLY-AMPK network in regulating energy homoeostasis that could be exploited pharmacologically. 213 Indeed, several AMPK-activating therapies such as metformin have shown anticancer and anti-inflammatory properties, and importantly are well tolerated in patients.…”
Section: Therapeutically Exploiting Fatty Acid Metabolism In Cancermentioning
confidence: 99%
“…For instance, in CRPC cells, inhibition of ACLY disrupts ER and energy homoeostasis in CRPC cells, leading to AMPK activation and sensitisation to androgen receptor inhibitors. 213 Intriguingly, supplementation of exogenous FAs is sufficient to restore hormone resistance in CRPC cells by alleviating the ER and energy stress instigated by ACLY inhibition, demonstrating the importance of an ACLY-AMPK network in regulating energy homoeostasis that could be exploited pharmacologically. 213 Indeed, several AMPK-activating therapies such as metformin have shown anticancer and anti-inflammatory properties, and importantly are well tolerated in patients.…”
Section: Therapeutically Exploiting Fatty Acid Metabolism In Cancermentioning
confidence: 99%
“…A recent study has demonstrated that it is possible to target the ACLY-AMPK-AR axes to sensitise CRPC cells to AR antagonism (65). A combined pharmacological approach with an AR antagonist and ACLY inhibition in CRPC cells promotes energetic stress and AMPK activation, resulting in further suppression of AR levels and target gene expression, inhibition of proliferation, and apoptosis.…”
Section: Key Regulators Of Lipid Metabolism In Pcmentioning
confidence: 99%
“…Silencing or inhibition of ACLY suppresses the proliferation of many cancer cell lines and impairs tumor growth (Bauer et al, 2005; Hanai et al, 2012; Hatzivassiliou et al, 2005; Migita et al, 2008; Shah et al, 2016; Zaidi et al, 2012). Depending on context, ACLY silencing or inhibition can also promote senescence (Lee et al, 2015), induce differentiation (Hatzivassiliou et al, 2005), or suppress cancer stemness (Hanai et al, 2013), further pointing to its potential as a target for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%